Report on the American Association of Medical Physics Undergraduate Fellowship Programs. (7th January 2013) - Smilowitz, Jennifer B.; Avery, Stephen; Gueye, Paul; Sandison, George A.
Abstract : The American Association of Physicists in Medicine (AAPM) sponsors two summer undergraduate research programs to attract top performing undergraduate students into graduate studies in medical physics: the Summer Undergraduate Fellowship Program (SUFP) and the Minority Undergraduate Summer Experience (MUSE). Undergraduate research experience (URE) is an effective tool to encourage students to pursue graduate degrees. The SUFP and MUSE are the only medical physics URE programs. From 2001 to 2012, 148 fellowships have been awarded and a total of 608, 000 has been dispersed to fellows. This paper reports on the history, participation, and status of the programs. A review of surveys of past fellows is presented. Overall, the fellows and mentors are very satisfied with the program. The efficacy of the programs is assessed by four metrics: entry into a medical physics graduate program, board certification, publications, and AAPM involvement. Sixty‐five percent of past fellow respondents decided to pursue a graduate degree in medical physics as a result of their participation in the program. Seventy percent of respondents are currently involved in some educational or professional aspect of medical physics. Suggestions for future enhancements to better track and maintain contact with past fellows, expand funding sources, and potentially combine the programs are presented. PACS number: 01.10.Hx